THREE NEW BOMOLOCHIDS PARASITIC ON FISHES OF THE KERALA COAST - Pillai, N Krishna (Indian Journal of Fisheries, 2011)
Three bomoloohids, Holobomolochus nemipteri sp. nov, Nothohomolochus quadricerossp. nov, and N. genesi sp. nov parasitic on tlie flslies of the Kerala coast are described